Women are underrepresented in fields where success is believed to require brilliance - Meyer, Meredith; Cimpian, Andrei; Leslie, Sarah-Jane (Frontiers in Psychology, 2015)
Women’s underrepresentation in science, technology, engineering, and mathematics (STEM) fields is a prominent concern in our society and many others. Closer inspection of this phenomenon reveals a more nuanced picture, however, with women achieving parity with men at the PhD level in certain STEM fields, while also being underrepresented in some non-STEM fields. It is important to consider and provide an account of this field-by-field variability. The Field-specific Ability Beliefs (FAB) hypothesis aims to provide such an account, proposing that women are likely to be underrepresented in fields thought to require raw intellectual talent—a sort of talent that women are stereotyped to possess less of than men. In two studies, we provide evidence for the FAB hypothesis, demonstrating that the academic fields believed by laypeople to require brilliance are also the fields with lower female representation. We also found that the field-specific ability beliefs of participants with college-level exposure to a field were more predictive of its female representation than those of participants without college exposure, presumably because the former beliefs mirror more closely those of the field’s practitioners (the direct “gatekeepers”). Moreover, the field-specific ability beliefs of participants with college exposure to a field predicted the magnitude of the field’s gender gap above and beyond their beliefs about the level of mathematical and verbal skills required. Finally, we found that beliefs about the importance of brilliance to success in a field may predict its female representation in part by fostering the impression that the field demands solitary work and competition with others. These results suggest new solutions for enhancing diversity within STEM and across the academic spectrum.